ANALISIS RELOKASI PASAR TERHADAP PENDAPATAN PEDAGANG DI PASAR RAKYAT KOTA PARIAMAN - Erniwati, Erniwati; Parlindungan S, Gokma Toni; Darsono, Rio (Ensiklopedia of Journal, 2023)
Traditional markets are markets that are traditional in nature where sellers and buyers can bargain directly, buildings usually consist of stalls, outlets, stalls and open platforms opened by sellers and market managers. Pasar Rakyat is one of the markets in Kota Pariaman which is located on Jl. St. Syahrir No. Kelurahan, Kp. Perak, Kec. Central Pariaman, in 2019 the People's Market was built by the City Government without eliminating the history of the United Market.This study uses data sourced from primary data and secondary data. The data collection method uses interviews, observation and documentation with 81 people's market traders as informants. The data analysis method used in this study is a qualitative descriptive method. The results of this study state that the government's policy towards relocation is good, but there is a decrease in the income of traders after being relocated due to the lack of visitors due to the large number of illegal traders selling in front of the market so that consumers are reluctant to enter the People's Market. Besides that, the small number of kiosks that were built meant that traders only sold a few of their wares, with the limit of asbestos stalls being easily broken and the lack of air ventilation so that the air was hot on the 2nd and 3rd floors.Keywords: People's Market, Market Relocation, Merchant Income